2007
DOI: 10.1016/j.bone.2006.10.025
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of quantitative computed tomography-based measures in predicting vertebral compressive strength

Abstract: Patient-specific measures derived from quantitative computed tomography (QCT) scans are currently being developed as a clinical tool for vertebral strength prediction. QCT-based measurement techniques vary greatly in structural complexity and generally fall into one of three categories: 1) bone mineral density (BMD), 2) "mechanics of solids" (MOS) models, such as minimum axial rigidity (the product of axial stiffness and vertebral height), or 3) three dimensional finite element (FE) models. There is no clear c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
121
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(136 citation statements)
references
References 35 publications
13
121
2
Order By: Relevance
“…In this study, we modeled Ea as BMD 2 where BMD is the integral BMD of a region and where NCSI equals BMD 2 multiplied by MNCS and TCSI equals BMD 2 multiplied by MXCS. TCSI has been validated against femoral strength in vitro by Lotz et al [8] and for vertebrae by Buckley et al [9]. Although prospective studies are needed, our results suggest a significant treatment effect with zoledronic acid on all three of these key indices, and the increase in volumetric BMD is consistent with expectation of an increase in the compressive strength.…”
Section: Discussionsupporting
confidence: 83%
“…In this study, we modeled Ea as BMD 2 where BMD is the integral BMD of a region and where NCSI equals BMD 2 multiplied by MNCS and TCSI equals BMD 2 multiplied by MXCS. TCSI has been validated against femoral strength in vitro by Lotz et al [8] and for vertebrae by Buckley et al [9]. Although prospective studies are needed, our results suggest a significant treatment effect with zoledronic acid on all three of these key indices, and the increase in volumetric BMD is consistent with expectation of an increase in the compressive strength.…”
Section: Discussionsupporting
confidence: 83%
“…Strength obtained from FE analyses predicted 76 % of the variation in bone strength, which also is less than the local measures. The correlation between FE and experimental results found here is in accordance with previous studies [28,[36][37][38][39][40]; Dall'Ara et al (2010) found a determination coefficient of 0.79 between FE-predicted vertebral strength and experimental values. It should be emphasized that the locations that we identified as the best predictor for vertebral strength represent the microstructure of the bone in a 4-mm spherical region around the element centroid.…”
Section: Discussionsupporting
confidence: 93%
“…The discrepancy can be explained by distinct experimental set-ups and distinct levels of disc degeneration. While embedding of isolated vertebrae ensures well-defined loading conditions (Buckley et al 2007), the test of the spinal segments is not as controlled. Moreover, the degeneration grading of the IVDs does not necessarily reflects its mechanical properties (Maquer et al 2014b).…”
Section: Discussionmentioning
confidence: 99%